Emerging role of epithelial-mesenchymal transition in hepatic cancer. Issue 1 (December 2016) - Yoshida, Go
Abstract Accumulating evidence suggests that the phenomenon of epithelial-mesenchymal-transition (EMT) plays a fundamental role in the tumor development. Several research articles have been published from Journal of Experimental and Clinical Cancer Research (JECCR) which have investigated into the molecular machineries underlying the importance of EMT for hepatic cancer. Given those recent publications by JECCR, this commentary focuses on the pathological significance of EMT for liver tumor.